Echocardiographic Evaluation of Transitional Circulation for the Neonatologists - Singh, Yogen; Tissot, Cécile (Frontiers in Pediatrics, 2018)
The hemodynamic changes during the first few breaths after birth are probably the most significant and drastic adaptation in the human life. These changes are critical for a smooth transition of fetal to neonatal circulation. With the cord clamping, lungs take over as the source of oxygenation from placenta. A smooth transition of circulation is a complex mechanism and primarily depends upon the drop in pulmonary vascular resistance and increase in systemic vascular resistance. Understanding the normal transition physiology and the adverse adaptation is of utmost importance to the clinicians looking after neonates. It may have a significant influence on the presentation of congenital heart defects in infants. Bedside echocardiography may help in understanding the transition physiology, especially the hemodynamic changes and shunting across ductus arteriosus and foramen ovale, and it may play an important role in making judicious clinical decisions based upon the altered physiology.